PENGARUH PENANAMAN MODAL ASING, PENANAMAN MODAL DALAM NEGERI, DAN PENDAPATAN ASLI DAERAH TERHADAP PERTUMBUHAN EKONOMI - Dewi, Ratna Sari; Sriwardani, Sriwardani (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2017)
The objective of this researchâs to understand and analyze Foreign Investment, Domestic Investment and locally-generated revenue significantly affect the economic growth in indonesiaâs provincial goverment. The population was 34 province in Indonesia since 2013 to 2015. The 33 sample was chosen using Purposive Sampling Sechnique. The data were processed by using multiple linear regression tests with an SPSS software program. The result of the research showed that Foreign Investment, Domestic Investment and locally-generated revenue has a significant and positive influence either itâs partially or simultaneously.Keywords: Foreign Investment, Domestic Investment, locally generated revenue, economic growth.